Patterns of Species Diversity are not Consistent between Shifting Cultivation in Bawangling Nature Reserves and Selective Logging in Diaoluoshan Nature Reserves, Hainan Island, China. (June 2016) - Lin, Deng; Jiang, Yong; Zang, Runguo; Wang, Xu; Long, Wenxing; Huang, Jin; Kang, Yong; Wang, Xixi; Xie, Zhixu
Examining changes in plant species diversity after shifting cultivation and logging has taken place in a system can help generate an understanding of the differences in species' responses to these human disturbances. We established 17 plots (each 0.25 hm 2 ) in young, middle-aged and old-growth forests (i.e. three recovery stages) in Bawangling and Diaoluoshan on Hainan Island, China, after shifting cultivation and selective logging had taken place. We divided each plot into four vertical communities. Changes in the species diversity of each plot (i.e. the overall community) and within the vertical communities were assessed across the three recovery stages. Results showed that, after shifting cultivation, species diversity increased across the three recovery stages for the overall community and for the four vertical communities. Species abundance decreased for the overall community but change was inconsistent for the four vertical communities. After selective logging, however, there was generally little change in species diversity and abundance across the three recovery stages, either overall or within the vertical communities. This suggests that patterns of species diversity between communities are different after shifting cultivation has occurred and when selective logging has taken place. Furthermore, Non-Metric Multidimensional Scaling showed differences in species composition across the three stages in the four vertical communities after shifting cultivation, but no differences in species composition across the three stages after selective logging. We also divided species dissimilarity coefficients into two parts, showing changes in species composition and abundance between the vertical communities under canopies and the canopy communities. We found that after shifting cultivation the coefficients between young-aged and old-growth forests, and middle-aged and old-growth forests were more than 0.77, but that they did not differ after selective logging had occurred. This suggests that changes in species turnover is unpredictable after shifting cultivation, but predictable after selective logging.